STUDENT’S SPEAKING ABILITY THROUGH THREE STEP INTERVIEW TECHNIQUE AT EFL CLASSROOM - Citra Prasiska Puspita Tohamba; lilis . (Metacommunication: Journal of Communication Studies, 2019)
ABSTRACT                 Three Step Interview technique in this study was classroom action research (CAR). This study was used two cycles; the first cycle consisted of three meeting for study and one meeting for evaluation test. The procedure of each cycle consists planning, action, observation, evaluation and reflection. The purpose of the researcher was to investigate whether the use of Three Step Interview[Must it be capitalized?] technique can improve student’s speaking ability in SMAN 1 Asera. There were 28 students, which is 6 males and 22 females. The instrument that used in this study was speaking test, observation sheet, and photograph. The researcher found that through Three Step Interview technique at eleventh grade of SMAN 1 ASERA could improve student’s speaking ability. It was evidence by the students achievement in the first cycle which was 55,57% ≤ 75. This indicates that Three Step Interview Technique could improve student’s speaking ability.Keywords:  speaking, cooperative learning, three step interview